2011
DOI: 10.1097/jto.0b013e318213f86a
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Adverse Events Among Elderly Patients Receiving Concurrent Chemoradiotherapy for Locally Advanced Non-small Cell Lung Cancer: Analysis of the Okayama Lung Cancer Study Group Trial 0007

Abstract: Chemotherapy with concurrent RT may be effective and tolerable in elderly patients with locally advanced non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…There remain controversial results regarding age factors (Table 3). Several studies have reported that CCRT could benefit appropriately selected elderly patients [14,16]. In a subgroup analysis of elderly patients (≥75 years), the median survival time was 31 months for those with adequate pulmonary function (DL CO > 80%), with a small tumor volume (GTV < 100 cm 3 ).…”
Section: Patient Fitness and Age Restrictions For Ccrtmentioning
confidence: 99%
“…There remain controversial results regarding age factors (Table 3). Several studies have reported that CCRT could benefit appropriately selected elderly patients [14,16]. In a subgroup analysis of elderly patients (≥75 years), the median survival time was 31 months for those with adequate pulmonary function (DL CO > 80%), with a small tumor volume (GTV < 100 cm 3 ).…”
Section: Patient Fitness and Age Restrictions For Ccrtmentioning
confidence: 99%
“…In our data, there was no difference between age groups in the incidence of severe esophageal toxicity ≥Grade 3, while the patients aged older than 75 experienced more frequent severe lung toxicity. However, CCRT could benefit appropriately selected elderly patients (17). In a subgroup analysis of elderly patients (>75 years) in our study, the median survival time was 31 months for those with adequate pulmonary function (DLCO > 80%), with a small tumor volume (GTV < 100 cm 3 ), and without subcarinal lymph node involvement.…”
Section: Discussionmentioning
confidence: 85%
“…Both trials consisted almost entirely of patients with PS 0 to 1, and the treatment was given with curative intent (radiation 60 Gy). 25,29 In a subanalysis of a phase III trial, Jalal et al 30 …”
Section: Discussionmentioning
confidence: 99%